Abstracts of the 20th Annual Meeting of the German Society for Radiation Oncology (DEGRO), 3-4 July, 2014, Dusseldorf, Germany 20. Jahrestagung der Deutschen Gesellschaft für Radioonkologie - Deloch, Lisa; Derer, Anja; Rühle, Paul-Friedrich; Ott, Oliver; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2014)
Created from Fastlane, Scopus look-up

Accelerated Partial Breast Irradiation: Frequent non-professional Phagocytosis in Patients with early, Hormone Receptor-positive Breast Cancer is associated with good Survival - Bauer, Marcus; Schnellhardt, S.; Rosahl, M. -C; Erber, Ramona; Ott, Oliver; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated Partial Breast Irradiation: Identification of High Risk Tumors in Early Hormone Receptor-positive Breast Cancer by Macrophage Shift Classification - Schnellhardt, S.; Erber, Ramona; Büttner-Herold, Maike; Rosahl, M. -C; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, L.; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated partial breast irradiation: Macrophage polarisation shift classification identifies high-risk tumours in early hormone receptor-positive breast cancer - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2020)
Studies have demonstrated correlations between accumulations of tumour-associated macrophages (TAMs), especially of M2-like phenotype, and increased mortality in advanced breast cancer. We investigated the prognostic potential of both main macrophage phenotypes in early hormone receptor-positive (HR+) breast cancer. The studied cohort of 136 patients participated in an institutional APBI phase II trial. Patient selection was characterized by HR+, small tumour size and no metastasis. Tissue microarrays from pre-RT resection samples were double stained for CD68/CD163 using immunohistochemistry. CD68+/CD163− cells were considered M1-like macrophages and CD68+/CD163+ was representative of M2-like macrophages. M1 and M2 macrophage densities were analysed semi-automatically in the stromal and intraepithelial tumour compartment. Low M1 and high M2 densities were strongly associated with decreased disease-free survival (DFS). Combined TAM phenotype densities were studied after defining a macrophage shift classification: M1-shifted (M1 high, M2 low) and non-shifted (M1 low, M2 low; M1 high, M2 high) tumours entailed a favourable outcome. In contrast, M2-shifted (M1 low, M2 high) TAM populations were associated with extremely reduced DFS. Thus, the full predictive potential of TAMs was revealed in a combined analysis of both phenotypes. The M2-shifted subgroup of tumours is classified as high-risk and probably not suitable for partial breast irradiation.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Accelerated partial breast irradiation; CD163; CD68; Early breast cancer; Hormone receptor-positive; Prognosis; Tumour associated macrophages

Accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy compared with whole-breast irradiation with boost for early breast cancer: 10-year results of a GEC-ESTRO randomised, phase 3, non-inferiority trial - Strnad, Vratislav; Polgár, Csaba; Ott, Oliver; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Łyczek, Jarosław; Guinot, Jose Luis; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgäuer, Michael; et al. (The Lancet. Oncology, 2023)
BACKGROUND: Several randomised, phase 3 trials have investigated the value of different techniques of accelerated partial breast irradiation (APBI) for patients with early breast cancer after breast-conserving surgery compared with whole-breast irradiation. In a phase 3 randomised trial, we evaluated whether APBI using multicatheter brachytherapy is non-inferior compared with whole-breast irradiation. Here, we present the 10-year follow-up results. METHODS: We did a randomised, phase 3, non-inferiority trial at 16 hospitals and medical centres in Austria, Czech Republic, Germany, Hungary, Poland, Spain, and Switzerland. Patients aged 40 years or older with early invasive breast cancer or ductal carcinoma in situ treated with breast-conserving surgery were centrally randomly assigned (1:1) to receive either whole-breast irradiation or APBI using multicatheter brachytherapy. Whole-breast irradiation was delivered in 25 daily fractions of 50 Gy over 5 weeks, with a supplemental boost of 10 Gy to the tumour bed, and APBI was delivered as 30·1 Gy (seven fractions) and 32·0 Gy (eight fractions) of high-dose-rate brachytherapy in 5 days or as 50 Gy of pulsed-dose-rate brachytherapy over 5 treatment days. Neither patients nor investigators were masked to treatment allocation. The primary endpoint was ipsilateral local recurrence, analysed in the as-treated population; the non-inferiority margin for the recurrence rate difference (defined for 5-year results) was 3 percentage points. The trial is registered with ClinicalTrials.gov, NCT00402519; the trial is complete. FINDINGS: Between April 20, 2004, and July 30, 2009, 1328 female patients were randomly assigned to whole breast irradiation (n=673) or APBI (n=655), of whom 551 in the whole-breast irradiation group and 633 in the APBI group were eligible for analysis. At a median follow-up of 10·36 years (IQR 9·12-11·28), the 10-year local recurrence rates were 1·58% (95% CI 0·37 to 2·8) in the whole-breast irradiation group and 3·51% (1·99 to 5·03) in the APBI group. The difference in 10-year rates between the groups was 1·93% (95% CI -0·018 to 3·87; p=0·074). Adverse events were mostly grade 1 and 2, in 234 (60%) of 393 participants in the whole-breast irradiation group and 314 (67%) of 470 participants in the APBI group, at 7·5-year or 10-year follow-up, or both. Patients in the APBI group had a significantly lower incidence of treatment-related grade 3 late side-effects than those in the whole-breast irradiation group (17 [4%] of 393 for whole-breast irradiation vs seven [1%] of 470 for APBI; p=0·021; at 7·5-year or 10-year follow-up, or both). At 10 years, the most common type of grade 3 adverse event in both treatment groups was fibrosis (six [2%] of 313 patients for whole-breast irradiation and three [1%] of 375 patients for APBI, p=0·56). No grade 4 adverse events or treatment-related deaths have been observed. INTERPRETATION: Postoperative APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is a valuable alternative to whole-breast irradiation in terms of treatment efficacy and is associated with fewer late side-effects. FUNDING: German Cancer Aid, Germany.
CRIS-Team Scopus Importer:2023-03-10

Analysis of antioxidant Factors in Patients' Blood with chronic Degenerative and inflammatory Diseases in the Course of Low-Dose Radiotherapy - Hehlgans, S.; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Oppermann, J.; Ott, Oliver; Weissmann, T.; Dilovic, E.; Roedel, C.; Gaipl, Udo; Fournier, C.; Roedel, F. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Analysis of the analgesic Effects of LDRT in Patients in the IMMO-LDRT01 Study - Fröhlich, Birgitta; Donaubauer, Anna-Jasmina; Weissmann, T.; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Analysis of the Expression of anti-oxidative Factors in the Blood of Patients with chronic degenerative and inflammatory Diseases before and after Low-dose Irradiation - IMMO-LDRT01 Study - Hehlgans, S.; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Ott, Oliver; Weissmann, Thomas; Fournier, C.; Gaipl, Udo; Roedel, F. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

An Analysis of the Use Pattern of Hyperthermia (HT) in Combination with Radio(chemo)therapy or Chemotherapy in European HT Centers - Ademaj, A.; Veltsista, D. P.; Marder, D.; Haelg, R. A.; Puric, E.; Brunner, T. B.; Crezee, H.; Gabrys, D.; Franckena, M.; Gani, C.; Horsman, M. R.; Krempien, R.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

An extension to the OVH concept for knowledge-based dose volume histogram prediction in lung tumor volumetric-modulated arc therapy - Brand, Johann; Szkitsak, Juliane; Ott, Oliver; Bert, Christoph; Speer, Stefan (Journal of Applied Clinical Medical Physics, 2025)
Purpose: Volumetric-modulated arc therapy (VMAT) treatment planning allows a compromise between a sufficient coverage of the planning target volume (PTV) and a simultaneous sparing of organs-at-risk (OARs). Particularly in the case of lung tumors, deciding whether it is possible or worth spending more time on further improvements of a treatment plan is difficult. Therefore, this work aims to develop a knowledge-based, structure-dependent, automated dose volume histogram (DVH) prediction module for lung tumors. Methods: The module is based on comparing geometric relationships between the PTV and the surrounding OARs. Therefore, treatment plan and structure data of 106 lung cancer cases, each treated in 28 fractions and 180 cGy/fx, were collected. To access the spatial information, a two-dimensional metric named overlap volume histogram (OVH) was used. Due to the rotational symmetry of the OVH and the typically coplanar setup of the VMAT technique, OVH is complemented by the so-called overlap-z-histogram (OZH). A set of achievable DVHs is predicted by identifying plans in the database with similar OVH and OZH. By splitting the dataset into a test set of 22 patients and a training set of 84 patients, the prediction capability of the OVH-OZH combination was evaluated. For comparison between the predicted and achieved DVH curves the coefficient of determination R2 was calculated. Results: The total lung showed strong linearity between predicted and achieved DVH curves for the OVH-OZH combination, resulting in a (Formula presented.) value close to 1 (0.975 ± 0.022). The heart benefits the most of the OZH resulting in a high prediction capability, with a higher (Formula presented.) of 0.962 ± 0.036 compared to the prediction with OVH only (0.897 ± 0.087). Conclusion: The combination of OZH and OVH was suitable for building a knowledge-based automated DVH prediction module. Implementing this method into the clinical workflow of treatment planning will contribute to advancing the quality of VMAT plans.
CRIS-Team Scopus Importer:2025-04-18
Keywords: DVH prediction; lung tumor; VMAT

A patterns of care analysis of hyperthermia in combination with radio(chemo)therapy or chemotherapy in European clinical centers - Ademaj, Adela; Veltsista, Paraskevi D.; Marder, Dietmar; Haelg, Roger A.; Puric, Emsad; Brunner, Thomas B.; Crezee, Hans; Gabrys, Dorota; Franckena, Martine; Gani, Cihan; Horsman, Michael R.; Krempien, Robert; et al. (Strahlentherapie und Onkologie, 2022)
Purpose The combination of hyperthermia (HT) with radio(chemo)therapy or chemotherapy (CT) is an established treatment strategy for specific indications. Its application in routine clinical practice in Europe depends on regulatory and local conditions. We conducted a survey among European clinical centers to determine current practice of HT. Methods A questionnaire with 22 questions was sent to 24 European HT centers. The questions were divided into two main categories. The first category assessed how many patients are treated with HT in combination with radio(chemo)therapy or CT for specific indications per year. The second category addressed which hyperthermia parameters are recorded. Analysis was performed using descriptive methods. Results The response rate was 71% (17/24) and 16 centers were included in this evaluation. Annually, these 16 centers treat approximately 637 patients using HT in combination with radio(chemo)therapy or CT. On average, 34% (range: 3-100%) of patients are treated in clinical study protocols. Temperature readings and the time interval between HT and radio(chemo)therapy or CT are recorded in 13 (81%) and 9 (56%) centers, respectively. The thermal dose quality parameter "cumulative equivalent minutes at 43 degrees C" (CEM43 degrees C) is only evaluated in five (31%) centers for each HT session. With regard to treatment sequence, 8 (50%) centers administer HT before radio(chemo)therapy and the other 8 in the reverse order. Conclusion There is a significant heterogeneity among European HT centers as to the indications treated and the recording of thermometric parameters. More evidence from clinical studies is necessary to achieve standardization of HT practice.
CRIS-Team WoS Importer:2022-09-09

Assessing Organ-at-risk Auto-contouring Solutions: Which Metrics are most predictive of clinical Time Savings? - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Lamrani, Allison; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Ott, Oliver; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Bladder cancer - Fabian, Alexander; Domschikowski, Justus; Dunst, Jürgen; Ott, Oliver (Springer International Publishing, 2024)
This chapter offers insights into radiotherapy of patients with bladder cancer based on latest evidence and consensus guidelines. Emphasis is placed on radical radiotherapy in the context of organ-preserving trimodal therapy of muscle-invasive bladder cancer. Patient selection as well as dose and fractionation of radiotherapy are outlined. Guidance on target volume definition is presented in detail per gross tumor volume, clinical target volume, and planning target volume. This includes a discussion of elective nodal irradiation and whole vs. partial bladder radiotherapy. Adequate concepts of radiotherapy are also proposed for cases treated in palliative intent. Furthermore, special treatment techniques are introduced including image-guided radiotherapy and adaptive radiotherapy. Didactic figures accompany the chapter and aid to convey the role and principles of radiotherapy for bladder cancer.
CRIS-Team Scopus Importer:2024-12-06

Blasenerhaltende multimodale Therapiekonzepte - Ott, Oliver (TumorDiagnostik & Therapie, 2024)
CRIS-Team Scopus Importer:2024-05-17
Keywords: multimodale blasenerhaltende Therapiekonzepte; simultane Radiochemotherapie

Cell-In-Cell Structures in Early Breast Cancer Are Prognostically Valuable - Bauer, Mareike; Hildebrand, Laura; Rosahl, Marie-Charlotte; Erber, Ramona; Schnellhardt, Sören; Büttner-Herold, Maike; Putz, Florian; Ott, Oliver; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Cell-in-cell (CIC) structures in breast cancer have so far been studied in a small inhomogeneous patient population, suggesting the prognostic importance of CIC. In the present study, we focused on CIC in early hormone-sensitive breast cancer. With in vitro co-culture experiments, we compared the homotypic phagocytic capacity of two breast cancer cell lines to that of primary human fibroblasts. Afterward, we studied 601 tissue specimens from 147 patients participating in an institutional accelerated partial breast irradiation (APBI) phase II trial. Both breast cancer cell lines performed non-professional phagocytosis at a higher rate than primary human fibroblasts. In this study cohort, 93.2% of the patients had T1 tumours, and 6.8% had T2 tumours. CIC was found in 61.2% of the patients, with a CIC rate ranging from <1/mm2 to 556.5/mm2 with a mean of 30.9/mm2 ± 68.4/mm2. CIC structures were prognostically favourable for local recurrence-free survival and disease-free survival. Regarding metastasis-free survival, CIC-positive patients had an unfavourable prognosis. Subgroup analysis indicated a correlation between a high proliferation index and high CIC rates. CIC had the highest prognostic value in young breast cancer patients (p = 0.004). With this study, we provide further evidence of CIC as a prognostic marker in breast cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: accelerated partial breast irradiation; breast cancer; cell-in-cell; ionizing radiation; non-professional phagocytosis; radiotherapy

Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Clinical Evidence for Thermometric Parameters to Guide Hyperthermia Treatment - Ademaj, Adela; Veltsista, Danai P.; Ghadjar, Pirus; Marder, Dietmar; Oberacker, Eva; Ott, Oliver; Wust, Peter; Puric, Emsad; Hälg, Roger A.; Rogers, Susanne; Bodis, Stephan; Fietkau, Rainer; et al. (Cancers, 2022)
Hyperthermia (HT) is a cancer treatment modality which targets malignant tissues by heating to 40–43 °C. In addition to its direct antitumor effects, HT potently sensitizes the tumor to radiotherapy (RT) and chemotherapy (CT), thereby enabling complete eradication of some tumor entities as shown in randomized clinical trials. Despite the proven efficacy of HT in combination with classic cancer treatments, there are limited international standards for the delivery of HT in the clinical setting. Consequently, there is a large variability in reported data on thermometric parameters, including the temperature obtained from multiple reference points, heating duration, thermal dose, time interval, and sequence between HT and other treatment modalities. Evidence from some clinical trials indicates that thermal dose, which correlates with heating time and temperature achieved, could be used as a predictive marker for treatment efficacy in future studies. Similarly, other thermometric parameters when chosen optimally are associated with increased antitumor efficacy. This review summarizes the existing clinical evidence for the prognostic and predictive role of the most important thermometric parameters to guide the combined treatment of RT and CT with HT. In conclusion, we call for the standardization of thermometric parameters and stress the importance for their validation in future prospective clinical studies.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Clinical evidence; Hyperthermia; Preclinical data; Thermometric parameters

Complex-valued neural networks to speed-up MR thermometry during hyperthermia using Fourier PD and PDUNet - Khatun, Rupali; Chatterjee, Soumick; Bert, Christoph; Wadepohl, Martin; Ott, Oliver; Semrau, Sabine; Fietkau, Rainer; Nürnberger, Andreas; Gaipl, Udo; Frey, Benjamin (Scientific Reports, 2025)
Hyperthermia (HT) in combination with radio- and/or chemotherapy has become an accepted cancer treatment for distinct solid tumour entities. In HT, tumour tissue is exogenously heated to temperatures between 39 and 43 °C for 60 min. Temperature monitoring can be performed non-invasively using dynamic magnetic resonance imaging (MRI). However, the slow nature of MRI leads to motion artefacts in the images due to the movements of patients during image acquisition. By discarding parts of the data, the speed of the acquisition can be increased - known as undersampling. However, due to the invalidation of the Nyquist criterion, the acquired images might be blurry and can also produce aliasing artefacts. The aim of this work was, therefore, to reconstruct highly undersampled MR thermometry acquisitions with better resolution and with fewer artefacts compared to conventional methods. The use of deep learning in the medical field has emerged in recent times, and various studies have shown that deep learning has the potential to solve inverse problems such as MR image reconstruction. However, most of the published work only focuses on the magnitude images, while the phase images are ignored, which are fundamental requirements for MR thermometry. This work, for the first time, presents deep learning-based solutions for reconstructing undersampled MR thermometry data. Two different deep learning models have been employed here, the Fourier Primal-Dual network and the Fourier Primal-Dual UNet, to reconstruct highly undersampled complex images of MR thermometry. MR images of 44 patients with different sarcoma types who received HT treatment in combination with radiotherapy and/or chemotherapy were used in this study. The method reduced the temperature difference between the undersampled MRIs and the fully sampled MRIs from 1.3 to 0.6 °C in full volume and 0.49 °C to 0.06 °C in the tumour region for a theoretical acceleration factor of 10.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Complex image; Deep learning; Hyperthermia; MR image reconstruction; MR reconstruction; MR thermometry; MRI; Undersampled; Undersampled MRI

Corrigendum: Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial(Front. Immunol., (2021), 12, (740742), 10.3389/fimmu.2021.740742) - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2022)
In the original article, there was an error. The mistake is found in the sentence “While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells.” in the abstract of the article.
CRIS-Team Scopus Importer:2022-03-04
Keywords: chronic degenerative and inflammatory diseases; immune status; immunophenotyping; low dose radiation therapy (LDRT); subjective pain level; x-rays

Deep Learning-based Auto-contouring of Lymph Node Levels in Head and Neck Area - Weissmann, Thomas; Huang, Yixing; Sommer, Phillip; Roesch, Johannes; Mansoorian, Sina; Ayala, H.; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Haderlein, Marlen; Hecht, Markus; Speer, Stefan; Schweizer, Claudia; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Defnitive Radiochemotherapy with and without regional Deep Hyperthermia of Bladder Carcinoma in elderly Patients - Siavooshhaghighi, H.; Putz, Florian; Gryc, Thomas; Mansoorian, S.; Filimonova, Irina; Fietkau, Rainer; Ott, Oliver (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

De-intensification of postoperative radiotherapy in head and neck cancer irrespective of human papillomavirus status—results of a prospective multicenter phase II trial (DIREKHT Trial) - Haderlein, Marlen; von der Grün, Jens; Balermpas, Panagiotis; Rödel, Claus; Hautmann, Matthias G.; Steger, Felix; Bohr, Christopher; Hehr, Thomas; Stromberger, Carmen; Budach, Volker; Schymalla, Markus; Engenhart-Cabillic, Rita; et al. (Frontiers in Oncology, 2024)
Background: Current standard treatment concepts in head and neck squamous cell carcinoma (HNSCC) are based on former studies using 2D and 3D treatment plans. However, modern radiation techniques allow for a more precise and individual dose application. Therefore, in a clearly defined patient population, de-intensified risk-adapted radiation is investigated. Methods: Patients with newly diagnosed HNSCC after surgery (with resection margins ≥1 mm and cM0) with the following tumor stages (TNM 7th Edition) were eligible for the study: oral cavity, oropharynx, or larynx: pT1–3, pN0–pN2b; hypopharynx: pT1–2, pN1. The patients should have either a low risk of local recurrence [≤pT2, resection margin ≥5 mm, no peritumoral lymphangiosis (L0), and no perineural invasion] or contralateral lymph node metastasis (≤3 ipsilateral lymph node metastases, in case of well-lateralized oropharyngeal or oral cavity cancer contralateral cN0, otherwise pN0). Patients were assigned to three different treatment regimes with reduction of the treated volume, radiation dose, or both, according to tumor stage and results of surgery performed. The primary objective was to show an LRR of <10% after 2 years. Findings: A total of 150 patients were enrolled. Tumor localizations were as follows: n = 53 (35.3%), oral cavity; n = 94 (62.7%), oropharynx (82% HPV-positive); n = 2 (1.3%), hypopharynx; and n = 1 (0.7%), larynx. A total of 61 patients (41.0%) were stage IVA, 81 (54.0%) were stage III, and 8 (5.3%) were stage II. Median follow-up was 36 months. Cumulative incidence of 2y-LRR was 5.6% (95% CI: 1.7%–9.2%) in the whole study population and 14.1% (95% CI: 3.8%–23.2%) in patients with oral cavity cancer. Cumulative incidence of 2y-LRR in non-irradiated or dose-reduced regions was 3.5% (95% CI: 0.4%–6.5%). After 2 years, disease-free survival was 92% (95% CI: 87%–96%) and overall survival was 94% (95% CI: 90%–98%) for the complete study cohort. Acute III° toxicity was as follows: dysphagia, 30%; xerostomia, 7%; mucositis, 19%; and dermatitis, 4%. Dysphagia and xerostomia decrease over time. After 27 months, late dysphagia III° and xerostomia II° were 1% and 9%, respectively. Interpretation: The study met its primary objective. De-intensification of postoperative radiotherapy irrespective of HPV status in a predefined patient population is associated with a favorable toxicity profile without compromising LRR. In an unplanned subgroup analysis, a significantly increased risk of LRR was observed in patients with oral cavity cancer. In these patients, de-intensified radiotherapy should be applied with caution.
CRIS-Team Scopus Importer:2024-09-13
Keywords: de-intensification; head and neck cancer; HPV; postoperative; radiotherapy

Development and clinical implementation of a digital system for risk assessments for radiation therapy - Kornek, Dominik; Menichelli, David; Leske, Jörg; Hofmann, Michael; Antkiewicz, David; Brandt, Tobias; Ott, Oliver; Lotter, Michael; Lang-Welzenbach, Marga; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2023)
Before introducing new treatment techniques, an investigation of hazards due to unintentional radiation exposures is a reasonable activity for proactively increasing patient safety. As dedicated software is scarce, we developed a tool for risk assessment to design a quality management program based on best practice methods, i.e., process mapping, failure modes and effects analysis and fault tree analysis. Implemented as a web database application, a single dataset was used to describe the treatment process and its failure modes. The design of the system and dataset allowed failure modes to be represented both visually as fault trees and in a tabular form. Following the commissioning of the software for our department, previously conducted risk assessments were migrated to the new system after being fully re-assessed which revealed a shift in risk priorities. Furthermore, a weighting factor was investigated to bring risk levels of the migrated assessments into perspective. The compensation did not affect high priorities but did re-prioritize in the midrange of the ranking. We conclude that the tool is suitable to conduct multiple risk assessments and concomitantly keep track of the overall quality management activities.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Failure modes and effects analysis (FMEA); Fault tree analysis (FTA); Process throughput; Radiation therapy; Risk analysis; Risk-based quality management

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Effect of hyperthermia and radiation therapy sequence on cell death and the immune phenotype of breast cancer cells - Sengedorj, Azzaya; Hader, Michael; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Scheidegger, S.; Barba, S. M.; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

External Beam Accelerated Partial Breast Irradiation in Early Breast Cancer and the Risk for Radiogenic Pneumonitis - Ott, Oliver; Stillkrieg, Wilhelm; Lambrecht, Ulrike; Sauer, Tim-Oliver; Schweizer, Claudia; Lamrani, Allison; Strnad, Vratislav; Hack, Carolin; Beckmann, Matthias; Uder, Michael; Fietkau, Rainer; Distel, Luitpold (Cancers, 2022)
Simple Summary Accelerated partial breast irradiation represents a well-established and safe treatment alternative for selected patients with early stage breast cancer after breast-conserving surgery. In a prospective trial on external beam partial breast irradiation, the risk for radiogenic pneumonitis is analyzed. After a median follow-up of 56 (1-129) months, radiogenic pneumonitis grade 2 appeared in only 1/170 (0.6%) patients. Compared to standard whole breast irradiation, the radiation doses applied to the lungs were very low. The patient with the radiogenic pneumonitis was found to have a generally increased radiation susceptibility. Using accelerated partial breast irradiation, the risk of radiogenic pneumonitis appeared quite low and may be limited to very exceptional cases associated with innate risk factors with an increased radiation susceptibility. In order to evaluate the risk for radiation-associated symptomatic pneumonitis in a prospective external beam accelerated partial breast irradiation (APBI) trial, between 2011 and 2021, 170 patients with early stage breast cancer were enclosed in the trial. Patients were eligible for study participation if they had a histologically confirmed breast cancer or an exclusive ductal carcinoma in situ (DCIS), a tumor size <= 3 cm, free safety margins >= 2 mm, no involved axillary lymph nodes, tumor bed clips, and were >= 50 years old. Patients received APBI with 38 Gy with 10 fractions in 10 consecutive working days. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Median follow-up was 56 (1-129) months. Ipsilateral lung MLD, V20, and V30 were 4.3 +/- 1.4 Gy, 3.0 +/- 2.0%, and 1.0 +/- 1.0%, respectively. Radiogenic pneumonitis grade 2 appeared in 1/170 (0.6%) patients two months after radiotherapy. Ipsilateral MLD, V20, and V30 were 6.1 Gy, 7, and 3% in this patient. Additionally, individual radiosensitivity was increased in this specific patient. Compared to WBI, APBI leads to lower lung doses. Using APBI, the risk of symptomatic radiogenic pneumonitis is very low and may be limited, with an ipsilateral V20 < 3% to very exceptional cases associated with innate risk factors with an increased radiation susceptibility.
CRIS-Team WoS Importer:2022-08-12

External-Beam-Accelerated Partial-Breast Irradiation Reduces Organ-at-Risk Doses Compared to Whole-Breast Irradiation after Breast-Conserving Surgery - Ott, Oliver; Stillkrieg, Willy; Lambrecht, Ulrike; Schweizer, Claudia; Lamrani, Allison; Sauer, Tim-Oliver; Strnad, Vratislav; Bert, Christoph; Hack, Carolin; Beckmann, Matthias; Fietkau, Rainer (Cancers, 2023)
In order to evaluate organ-at-risk (OAR) doses in external-beam-accelerated partial-breast irradiation (APBI) compared to standard whole-breast irradiation (WBI) after breast-conserving surgery. Between 2011 and 2021, 170 patients with early breast cancer received APBI within a prospective institutional single-arm trial. The prescribed dose to the planning treatment volume was 38 Gy in 10 fractions on 10 consecutive working days. OAR doses for the contralateral breast, the ipsilateral, contralateral, and whole lung, the whole heart, left ventricle (LV), and the left anterior descending coronary artery (LAD), and for the spinal cord and the skin were assessed and compared to a control group with real-world data from 116 patients who underwent WBI. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Compared to WBI, APBI led to reduced OAR doses for the contralateral breast (0.4 ± 0.6 vs. 0.8 ± 0.9 Gy, p = 0.000), the ipsilateral (4.3 ± 1.4 vs. 9.2 ± 2.5 Gy, p = 0.000) and whole mean lung dose (2.5 ± 0.8 vs. 4.9 ± 1.5 Gy, p = 0.000), the mean heart dose (1.6 ± 1.6 vs. 1.7 ± 1.4 Gy, p = 0.007), the LV V23 (0.1 ± 0.4 vs. 1.4 ± 2.6%, p < 0.001), the mean LAD dose (2.5 ± 3.4 vs. 4.8 ± 5.5 Gy, p < 0.001), the maximum spinal cord dose (1.5 ± 1.1 vs. 4.5 ± 5.7 Gy, p = 0.016), and the maximum skin dose (39.6 ± 1.8 vs. 49.1 ± 5.8 Gy, p = 0.000). APBI should be recommended to suitable patients to minimize the risk of secondary tumor induction and the incidence of consecutive major cardiac events.
CRIS-Team Scopus Importer:2023-08-25
Keywords: accelerated partial-breast irradiation; breast cancer; mean heart dose; mean lung dose; organs-at-risk

First clinical evaluation of breathing controlled four-dimensional computed tomography imaging - Szkitsak, Juliane; Werner, René; Fernolendt, Susanne; Schwarz, Annette; Ott, Oliver; Fietkau, Rainer; Hofmann, Christian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2021)
Background and Purpose: Four-dimensional computed tomography (4DCT) has become an essential part of radiotherapy planning but is often affected by artifacts. A new breathing controlled 4DCT (i4DCT) algorithm has been introduced. This study aims to present the first clinical data and to evaluate the achieved image quality, projection data coverage and beam-on time. Material & Methods: The analysis included i4DCT data for 129 scans of patients with thoracic tumors. Projection data coverage and beam-on time were evaluated. Additionally, image quality was exemplarily discussed and rated by ten clinical experts with a 5-score-scale for 30 patients with large variations in their breathing pattern (‘challenging subgroup’). Rated images were reconstructed amplitude- and phase-based. Results: Expert scoring revealed that 78% (amplitude-based) and 63% (phase-based) of the challenging subgroup were artifact-free (rating ≥4). For the entire cohort, average beam-on time per couch position was 4.9 ± 1.6 s. For the challenging subgroup, time increased slightly but not significantly compared to the remaining patients (5.1 s vs. 4.9 s; p = 0.64). Median projection data coverage was 93% and 94% for inhalation and exhalation, respectively, for the entire cohort. The comparison for the subgroup and the remaining patients revealed a small but significant decrease of the median coverage values for the challenging cases (inhalation: 90% vs. 94%, p = 0.02; exhalation: 93% vs. 94%, p = 0.02). Conclusions: This first clinical evaluation of i4DCT shows very promising results in terms of image quality and projection data coverage. The results agree with and support the results of previous i4DCT phantom studies.
CRIS-Team Scopus Importer:2021-11-12
Keywords: 4DCT; Motion artifacts; Respiratory motion

Hyperthermia in the treatment of high-risk soft tissue sarcomas: a systematic review - Veltsista, Paraskevi Danai; Oberacker, Eva; Ademaj, Adela; Corradini, Stefanie; Eckert, Franziska; Flörcken, Anne; Kaul, David; Lindner, Lars H.; Issels, Rolf; Ott, Oliver; Pink, Daniel; Potkrajcic, Vlatko; et al. (International Journal of Hyperthermia, 2023)
Background: The therapy of high-risk soft tissue sarcomas (STS) remains an interdisciplinary challenge. Regional hyperthermia (RHT) sparked interest as it has been shown to improve overall survival when added to perioperative chemotherapy (CTX). However, questions arise on how RHT should be optimally integrated into current multi-modal therapies. Materials and Methods: We performed a systematic literature review according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies written in English and focused mainly on radiative RHT and superficial hyperthermia were evaluated and included. Studies including patients below the age of 18, with metastatic disease or review articles, were excluded. Results: We identified 15 clinical reports from 1990 until July 2022. Three articles combined RHT + CTX, and twelve focused on combined RHT + radiotherapy (RT) or neoadjuvant chemoradiotherapy (CRT). Most treatments were based on invasive thermometry, and less on magnetic resonance imaging (MRI)-based, noninvasive thermometry for STS of the extremities. Perioperative chemotherapy was used for the combination of RHT and CTX, mostly Ifosfamide-based. The effectiveness of RT appeared to be increased by RHT, especially with two RHT sessions/week. The trimodal simultaneous approach of neoadjuvant RHT and CRT was also feasible. No significant toxicity of RHT was reported. Conclusions: The gathered data strengthen the beneficial role of RHT in the multimodal setting. Further expert consensus and clinical trials are required to determine the optimal integration of RHT in treating STS.
CRIS-Team Scopus Importer:2023-07-28
Keywords: chemotherapy; high-risk; Hyperthermia; radiation; sarcoma

Improving the safety of radiotherapy treatment processes via incident-driven FMEA feedback loops - Kornek, Dominik; Lotter, Michael; Szkitsak, Juliane; Dürrbeck, Christopher; Karius, Andre; Ott, Oliver; Brandl, Carolin; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2024)
Background: Failure mode and effects analysis (FMEA) is a valuable tool for radiotherapy risk assessment, yet its outputs might be unreliable due to failures not being identified or due to a lack of accurate error rates. Purpose: A novel incident reporting system (IRS) linked to an FMEA database was tested and evaluated. The study investigated whether the system was suitable for validating a previously performed analysis and whether it could provide accurate error rates to support the expert occurrence ratings of previously identified failure modes. Methods: Twenty-three pre-identified failure modes of our external beam radiotherapy process, covering the process steps from patient admission to treatment delivery, were proffered on dedicated FMEA feedback and incident reporting terminals generated by the IRS. The clinical setting involved a computed tomography scanner, dosimetry, and five linacs. Incoming reports were used as basis to identify additional failure modes or confirm initial ones. The Kruskal–Wallis H test was applied to compare the risk priorities of the retrospective and prospective failure modes. Wald's sequential probability ratio test was used to investigate the correctness of the experts’ occurrence ratings by means of the number of incoming reports. Results: Over a 15-month period, 304 reports were submitted. There were 0.005 (confidence interval [CI], 0.0014–0.0082) reported incidents per imaging study and 0.0006 (CI, 0.0003–0.0009) reported incidents per treatment fraction. Sixteen additional failure modes could be identified, and their risk priorities did not differ from those of the initial failure modes (p = 0.954). One failure mode occurrence rating could be increased, whereas the other 22 occurrence ratings could not be disproved. Conclusions: Our approach is suitable for validating FMEAs and deducing additional failure modes on a continual basis. Accurate error rates can only be provided if a sufficient number of reports is available.
CRIS-Team Scopus Importer:2024-08-23
Keywords: error rates; failure mode and effects analysis (FMEA); incident reporting system (IRS); radiotherapy; risk assessment

Interaction of Radiotherapy and Hyperthermia with the Immune System: a Brief Current Overview - Sengedorj, Azzaya; Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Rückert, Michael (Current Stem Cell Reports, 2022)
Purpose of Review This review focuses on the opposing effects on the immune system of radiotherapy (RT) and the consequences for combined cancer treatment strategies of RT with immunotherapies, including hyperthermia (HT). How RT and HT might affect cancer stem cell populations is also briefly outlined in this context.
CRIS-Team WoS Importer:2022-07-29

Is it time to redefine the role of low-dose radiotherapy for benign disease? - Montero, Angel; Sabater, Sebastia; Roedel, Franz; Gaipl, Udo; Ott, Oliver; Seegenschmiedt, Michael Heinrich; Arenas, Meritxell (Annals of the Rheumatic Diseases, 2020)
CRIS-Team WoS Importer:2020-03-27

LDRT induces long-lasting Pain and Immunomodulating Effects in chronic degenerative and inflammatory Diseases - Results from the IMMO-LDRT01 Study - Donaubauer, Anna-Jasmina; Weissmann, Thomas; Fröhlich, Birgitta; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Long‐term follow‐up of patients receiving neoadjuvant treatment modalties for soft tissue sarcomas of the extremities - Rauch, Miriam; Agaimy, Abbas; Semrau, Sabine; Willner, Alexander; Ott, Oliver; Fietkau, Rainer; Hohenberger, Werner; Croner, Roland S.; Grützmann, Robert; Fechner, Katja; Vassos, Nikolaos (Cancers, 2021)
Background: Neoadjuvant treatment modalities in soft tissue sarcoma (STS) of the extremities have become more popular in recent years, but because of the rarity and heterogeneity of STS, there are yet few studies on the long‐term impact of neoadjuvant treatment modalities, especially in terms of neoadjuvant radiochemotherapy. Methods: The study enrolled 136 patients with primary STS of the extremities who underwent surgery with curative intent or neoadjuvant therapy, followed by surgery in a 15‐year period. Neoadjuvant treatment consisted of radiotherapy (RT) with 60 Gy and in most cases simultaneous chemotherapy (CTx) with ifosfamide (1.5 g/m2/d, d1–5, q28) and doxorubicine (50 mg/m2/d, d3, q28). We investigated the clinical, (post)‐operative and histopathological data and the oncological follow‐up as well. The median follow‐up period was 82 months (range 6–202). Results: A total of 136 patients (M:F = 73:63) with a mean age of 62 years (range; 21–93) was observed. Seventy‐four patients (54.4%) received neoadjuvant therapy (NT), 62 patients (45.6%) received primary surgery (PS). When receiving NT, patients with high‐risk STS had a lower risk to develop distant metastasis (p = 0.025). Age, histological type, tumor size and surgical margins (R0 vs. R1) had no influence on any survival rates. There was an association between NT and the occurrence of postoperative complications (p = 0.001). The 5‐year local recurrence free survival (LRFS), metastasis free survival (MFS), disease free survival (DFS) and overall survival (OS) rate of the whole cohort was 89.9%, 77.0%, 70.6% and 72.6%; whereas the 5‐year LRFS, MFS, DFS and OS rate was 90.5%, 67.2%, 64.1% and 62.8% for the NT group and 89.5%, 88.3%. 78.4% and 83.8% for the PS group. Conclusion: Multimodal treatment strategies in patients with STS of extremities lead to excellent oncological outcomes. Patients with high‐risk STS had a significantly better MFS when receiving NT than patients with low‐risk STS. NT was associated with a higher probability of postoperative but well‐manageable complications.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Extremity; Neoadjuvant therapy; Radiation; Radiochemotherapy; Soft tissue sarcoma

Low-dose radiation therapy for COVID-19 pneumopathy: what is the evidence? - Roedel, Franz; Arenas, Meritxell; Ott, Oliver; Fournier, Claudia; Georgakilas, Alexandros G.; Tapio, Soile; Trott, Klaus-Ruediger; Gaipl, Udo (Strahlentherapie und Onkologie, 2020)
In the current dismal situation of the COVID-19 pandemic, effective management of patients with pneumonia and acute respiratory distress syndrome is of vital importance. Due to the current lack of effective pharmacological concepts, this situation has caused interest in (re)considering historical reports on the treatment of patients with low-dose radiation therapy for pneumonia. Although these historical reports are of low-level evidence per se, hampering recommendations for decision-making in the clinical setting, they indicate effectiveness in the dose range between 0.3 and 1 Gy, similar to more recent dose concepts in the treatment of acute and chronic inflammatory/degenerative benign diseases with, e.g., a single dose per fraction of 0.5 Gy. This concise review aims to critically review the evidence for low-dose radiation treatment of COVID-19 pneumopathy and discuss whether it is worth investigating in the present clinical situation.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Anti-inflammatory; COVID-19; Low-dose radiation therapy; Pneumonia; SARS-CoV-2

Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2021)
The treatment of chronic inflammatory and degenerative diseases by low dose radiation therapy (LDRT) is promising especially for patients who were refractory for classical therapies. LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has been applied since the late 19th century, the immunological mechanisms remain elusive. Within the prospective IMMO-LDRT01 trial (NCT02653079) the effects of LDRT on the peripheral blood immune status, as well as on pain and life quality of patients have been analyzed. Blood is taken before and after every serial irradiation with a single dose per fraction of 0.5Gy, as well as during follow-up appointments in order to determine a detailed longitudinal immune status by multicolor flow cytometry. Here, we report the results of an interim analysis of 125 patients, representing half the number of patients to be recruited. LDRT significantly improved patients' pain levels and induced distinct systemic immune modulations. While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells. Furthermore, activated immune cells were decreased following LDRT. Especially cells of the monocytic lineage correlated to LDRT-induced improvements of clinical symptoms, qualifying these immune cells as predictive biomarkers for the therapeutic success. We conclude that LDRT improves pain of the patients by inducing systemic immune modulations and that immune biomarkers could be defined for prediction by improved patient stratification in the future.
CRIS-Team WoS Importer:2021-11-12

Low-dose Radiotherapy for painful Finger Joint Arthrosis - Weissmann, T.; Ott, Oliver; Putz, Florian; Becker, Ina; Fietkau, Rainer; Donaubauer, Anna-Jasmina; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-09-25

Low-Dose Radiotherapy is highly effective in the Treatment of painful Finger Polyarthrosis - Weissmann, Thomas; Gaipl, Udo; Putz, Florian; Hecht, Markus; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Fietkau, Rainer; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose Radiotherapy is highly effective in the Treatment of Patients with painful Ankle Arthrosis - Weissmann, Thomas; Putz, Florian; Hecht, Markus; Zhou, Jianguo; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-Dose Radiotherapy Leads to a Systemic Anti-Inflammatory Shift in the Pre-Clinical K/BxN Serum Transfer Model and Reduces Osteoarthritic Pain in Patients - Weissmann, Thomas; Rückert, Michael; Zhou, Jianguo; Seeling, Michaela; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Nimmerjahn, Falk; Ott, Oliver; Hecht, Markus; Putz, Florian; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is the leading degenerative joint disease in the western world and leads, if left untreated, to a progressive deterioration of joint functionality, ultimately reducing quality of life. Recent data has shown, that especially OA of the ankle and foot are among the most frequently affected regions. Current research in OA points towards a complex involvement of various cell and tissue types, often accompanied by inflammation. Low-dose radiotherapy (LDRT) is widely used for the treatment of degenerative and inflammatory diseases. While the reported analgesic effects are well known, the underlying molecular mechanisms are only poorly understood. We therefore correlated a clinical approach, looking at pain reduction in 196 patients treated with LDRT with a pre-clinical approach, utilizing the K/BxN serum transfer mouse model using flow cytometry and multiplex ELISA for analysis. While an improvement of symptoms in the majority of patients was found, patients suffering from symptoms within the tarsi transversa show a significantly lower level of improvement. Further, a significant impact of therapy success was detected depending on whether only one or both feet were affected. Further, patients of younger age showed a significantly better outcome than older ones while needing fewer treatment series. When looking on a cellular level within the mouse model, a systemic alteration of immune cells namely a shift from CD8+ to CD4+ T cells and reduced numbers of DCs was observed. A general reduction of inflammatory cytokines was detected, with significant alterations in IL-4 and IL-17 levels, all of which could potentially be responsible for the highly effective clinical improvement in patients. Taken together our data indicate that LDRT can be regarded as a highly effective treatment option for patients suffering from OA of the foot and ankle, in terms of analgesic effects, especially in younger patients. Furthermore, the observed effects are mediated by an interplay of cellular and soluble immune factors, as observed in the K/BxN serum transfer model. With this interdisciplinary approach we aim to encourage the usage of LDRT as an additive treatment strategy not only as a last resort, but also earlier in the course of disease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: foot; K/BxN serum transfer; low-dose radiotherapy; mouse model; osteoarthritis; pain; rheumatoid arthritis; X-rays

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

Moderate Hypofractionation in Bladder Cancer - a new Standard of Care? - Ott, Oliver (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-07-23

Multimodality Treatment for Bladder Conservation - Ott, Oliver (Springer International Publishing, 2019)
Standard treatment for muscle-invasive urothelial cancer of the bladder is radical cystectomy. Multimodality treatment, including initial transurethral resection of the bladder tumor (TUR-B), followed by concurrent radiochemotherapy (RCT) has been shown to produce survival rates comparable to those of radical cystectomy. With these bladder conservation approaches, (salvage) cystectomy has been reserved for patients with incomplete response or local muscle-invasive relapse. During the past three decades, organ preservation by multimodality treatment has been investigated in prospective series from single centers and cooperative groups, with far more than 1000 patients included. Five-year overall survival rates in the range of 50–60% have been reported, and approximately 80% of the surviving patients maintained their own bladder. Clinical criteria helpful in determining patients for bladder preservation include such variables as small tumor size (<5 cm), early tumor stage, a visibly and microscopically complete transurethral resection, absence of ureteral obstruction, and no evidence of pelvic lymph node metastases. On multivariate analysis, the completeness of TUR-B was found to be one of the strongest predictive factors for overall survival. Patients at greater risk of recurrence after initial complete response are those with multifocal disease and extensive associated carcinoma in situ at presentation. Close coordination among all disciplines is required to achieve optimal results. Future investigations will focus on optimizing radiation techniques including all possibilities of radiosensitization (e.g., concurrent radiochemotherapy, additional deep regional hyperthermia), and incorporating more effective systemic chemotherapy, and proper selection of patients based on predictive molecular makers.
CRIS-Team Scopus Importer:2024-12-16

Neoadjuvant chemoradiation combined with regional hyperthermia in locally advanced or recurrent rectal cancer - Ott, Oliver; Gani, Cihan; Lindner, Lars H.; Schmidt, Manfred; Lamprecht, Ulf; Abdel-Rahman, Sultan; Hinke, Axel; Weissmann, Thomas; Hartmann, Arndt; Issels, Rolf D.; Zips, Daniel; Belka, Claus; et al. (Cancers, 2021)
Background: To prospectively analyze feasibility and pathological complete response (pCR) rates of neoadjuvant chemoradiotherapy combined with regional hyperthermia (RHT) in patients with locally advanced (LARC) or recurrent (LRRC) rectal cancer. Methods: between 2012 and 2018, 111 patients with UICC stage IIB-IV or any locally recurrent rectal cancer were included (HyRec-Trial, ClinicalTrials.gov Identifier: NCT01716949). Patients received radiotherapy with concurrent 5-Fluororuracil (5-FU)/Capecitabine and Oxaliplatin, and RHT. Stage 1 feasibility analysis evaluated dose-limiting toxicities (DLT) after 19 patients, stage 2 after 59 evaluable patients. Analysis of the pCR rate was based on histopathological reports. Results: the feasibility rates for stages 1 and 2 were 90% (17/19) and 73% (43/59), respectively. In the intention-to-treat population the pCR rate was 19% (20/105; 90% confidence interval (CI) 13.0–26.5). In the per-protocol-analysis, complete tumor regression was seen in 28% (18/64) and 38% (3/8) of the patients with LARC and LRRC, respectively. Complete resection rates (R0) among patients with LARC and LRRC who received surgery were 99% (78/84) and 67% (8/12). Conclusions: the intensified neoadjuvant and multimodality treatment schedule was feasible and led to comparable early toxicity rates as described by other trials that used the similar chemoradiation protocol. The presented treatment regimen resulted in a very high pCR rate and appears as a promising option for patients with LRRC.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Complete remission rate; Concurrent chemoradiation; Locally advanced rectal cancer; Locally recurrent rectal cancer; Regional hyperthermia; Tumor regression grading

Neoadjuvant chemoradiotherapy in combination with deep regional hyperthermia followed by surgery for rectal cancer: a systematic review and meta-analysis - Ademaj, Adela; Stieb, Sonja; Gani, Cihan; Ott, Oliver; Marder, Dietmar; Hälg, Roger A.; Rogers, Susanne; Ghadjar, Pirus; Fietkau, Rainer; Crezee, Hans; Riesterer, Oliver (Strahlentherapie und Onkologie, 2024)
Background and purpose: Combining chemoradiotherapy (CRT) with deep regional hyperthermia (HT) shows promise for enhancing clinical outcomes in selected rectal cancer patients. This study aimed to integrate the evidence and evaluate the efficacy of this combined treatment approach. Materials and methods: A systematic search of the PubMed, Scopus, and Mendeley databases was performed. This review was conducted according to the PRISMA guidelines. The quality of studies was evaluated using the Newcastle–Ottawa scale (NOS). Random-effects meta-analyses (DerSimonian and Laird) were performed. The primary outcome was pathological complete response (pCR), and secondary endpoints were overall survival (OS), disease-free survival (DFS), local recurrence-free survival (LRFS), and toxicity. Results: In total, 12 studies were included, mostly of moderate quality. Patients with locally advanced rectal cancer (LARC; n = 760) and locally recurrent rectal cancer (LRRC; n = 22) were eligible. The pooled pCR rate was 19% (95% confidence interval [CI]: 16–22%) among all 782 patients and 19% (95%CI:16–23%) among 760 LARC patients. Due to significant study heterogeneity, survival outcomes were pooled by excluding LRRC patients. The pooled 5‑year OS rate among 433 LARC patients was 87% (95%CI: 83–90%). The pooled 5‑year DFS and LRFS in LARC patients were 75% (95%CI: 70–80%) and 95% (95%CI: 92–97%), respectively. There was a lack of consistent reporting of HT treatment parameters and toxicity symptoms among the studies. Conclusion: The collective clinical evidence showed that neoadjuvant CRT combined with HT in rectal cancer patients is feasible, with a 19% pCR rate and excellent survival outcomes in long term follow-up.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Chemoradiotherapy; Deep regional hyperthermia; Locally advanced rectal cancer; Locally recurrent rectal cancer

Neoadjuvant concurrent chemoradiotherapy with and without hyperthermia in retroperitoneal sarcomas: feasibility, efficacy, toxicity, and long-term outcome - Willner, Alexander; Fechner, Katja; Agaimy, Abbas; Haller, Florian; Eckstein, Markus; Ott, Oliver; Putz, Florian; Gaipl, Udo; Kersting, S.; Meidenbauer, Norbert; Grützmann, Robert; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2021)
Purpose Retroperitoneal (RPS) sarcomas are associated with poor local and abdominal tumor control. However, the benefit of preoperative radio- or chemotherapy alone for these entities is currently unclear. Moreover, as intermediate- and high-grade sarcomas have a tendency toward early metastasis, exploration of neoadjuvant strategies is of high importance. This analysis reports the results of our 20-year single-institution experience with preoperative neoadjuvant concurrent chemoradiation. Methods From 2000-2019, 27 patients with intermediate- or high-grade RPS (12 dedifferentiated liposarcoma, 10 leiomyosarcoma, 5 others) were treated with radiotherapy (median dose: 50.4 Gy; range 45-75 Gy) and two cycles of chemotherapy (doxorubicin 50 mg/m(2) BSA/d3 q28 and ifosfamide 1.5 g/m(2) BSA/d1-5 q28) in neoadjuvant intent. Chemotherapy consisted of doxorubicin alone in two cases and ifosfamide alone in one case. Fifteen patients (56%) additionally received deep regional hyperthermia. Results The median follow-up time was 53 months (+/- 56.7 months). 92% of patients received two cycles of chemotherapy as planned and 92% underwent surgery. At 5 and 10 years, abdominal-recurrence-free survival was 74.6% (+/- 10.1%) and 66.3% (+/- 11.9%), distant metastasis-free survival was 67.2% (+/- 9.7%) and 59.7% (+/- 11.1%), and overall survival was 60.3% (+/- 10.5%) and 60.3% (+/- 10.5%), respectively. CTC grade III and IV toxicities were leukocytopenia (85%), thrombocytopenia (33%), and anemia (11%). There were no treatment-related deaths. Conclusion Neoadjuvant chemoradiotherapy with and without hyperthermia for retroperitoneal sarcomas is feasible and provided high local control of intermediate- and high-grade sarcoma.
CRIS-Team WoS Importer:2021-11-12

Neoadjuvante Radiochemotherapie kombiniert mit regionaler Tiefenhyperthermie beim Rektumkarzinom? - Ott, Oliver (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-09-24

Organ preservation after total neoadjuvant therapy for locally advanced rectal cancer (CAO/ARO/AIO-16): an open-label, multicentre, single-arm, phase 2 trial - Gani, Cihan; Fokas, Emmanouil; Polat, Bülent; Ott, Oliver; Diefenhardt, Markus; Königsrainer, Alfred; Böke, Simon; Kirschniak, Andreas; Bachmann, Robert; Wichmann, Dörte; Bitzer, Michael; Clasen, Stephan; et al. (Lancet Gastroenterology and Hepatology, 2025)
Background: Total neoadjuvant therapy has been shown to increase pathological complete response and disease-free survival in patients with locally advanced rectal cancer after total mesorectal excision (TME). We hypothesised that total neoadjuvant therapy could maximise the number of patients attaining a clinical complete response who could then be instead referred to organ preservation with watch and wait. Methods: This open-label, multicentre, single-arm, phase 2 study (CAO/ARO/AIO-16) was conducted at four centres across Germany. Patients aged 18 years or older with histologically confirmed cT1–2N1–2 or cT3a–dN0/N1–2 rectal adenocarcinoma up to 12 cm from the anal verge and without distant metastases received chemoradiotherapy. Radiotherapy was administered in daily fractions of 1·8 Gy, 5 days per week, starting at day 1 and ending at day 38, for a total of 28 fractions and total dose of 50·4 Gy. Concomitant fluorouracil (250 mg/m2 per day as a continuous venous infusion from day 1 to day 14 and day 22 to day 35) and oxaliplatin (50 mg/m2 intravenously on days 1, 8, 22, and 29) were administered. Chemoradiotherapy was followed by three cycles of consolidation FOLFOX (fluorouracil [2400 mg/m2 over 46 h by continuous venous infusion], oxaliplatin [100 mg/m2 intravenously as a 2-h infusion], and leucovorin [400 mg/m2 intravenously as a 2-h infusion]) starting on days 57, 71, and 85. Response assessment was scheduled on day 106 after the start of total neoadjuvant therapy and included digital rectal examination, rectoscopy, and pelvic MRI. In case of a clinical complete response, patients were scheduled for a watch and wait surveillance protocol. Patients with a near clinical complete response on day 106 were offered a second assessment on day 196. In case of conversion to a clinical complete response on this repeated assessment, the same watch and wait surveillance protocol was initiated. Alternatively, local excision was considered on day 196 if technically feasible. In all other cases, immediate TME surgery was recommended. The primary endpoint was the clinical complete response rate on day 106 or 196 assessed in patients who started chemoradiotherapy (intention-to-treat population). Toxicity was also assessed in this patient population. The study was registered with ClinicalTrials.gov (NCT03561142) and is complete. Findings: Between June 1, 2018, and Oct 7, 2020, we enrolled 93 patients, of whom 91 (mean age 61 years [SD 10]; 61 [67%] men and 30 [33%] women) started chemoradiotherapy, 88 started consolidation chemotherapy, and 88 had a response assessment on day 106. At this first assessment, 13 (15%) patients were classified as having a clinical complete response and were assigned to watch and wait, 33 (38%) met criteria for a near clinical complete response and were scheduled for reassessment, and 42 (48%) had a poor response and were referred for immediate TME. At the second assessment, on day 196, 21 (64%) of 33 patients converted to a clinical complete response, two underwent local excision with a pathological complete response (and were also assigned to watch and wait), and ten had TME. Therefore, for the primary endpoint, 34 (37%) of the initial 91 patients attained a clinical complete response after total neoadjuvant therapy. Overall, 33 (36%) of 91 patients developed grade 3 or 4 toxicity during total neoadjuvant therapy. 17 (19%) patients developed grade 3 toxicity during chemoradiotherapy, with no grade 4–5 toxicity occurring at this treatment stage. The most frequently reported grade 3 toxicities during chemoradiotherapy were diarrhoea in nine (10%) patients and infections in six (7%). During consolidation chemotherapy, 17 (19%) of 88 patients had grade 3 toxicities, the most common of which were leucopenia (in seven [8%] patients) and neutropenia (in seven [8%]). One (1%) patient had grade 4 neutropenia and one patient died of COVID-19-associated pneumonia. Grade 3 and grade 4 adverse events during follow-up were recorded in 19 (21%) of 91 patients. Interpretation: Upfront chemoradiotherapy and three cycles of consolidation FOLFOX result in a high rate of clinical complete response with an acceptable toxicity profile. Total neoadjuvant therapy combined with a watch and wait approach after a clinical complete response can be considered for patients with locally advanced rectal cancer seeking an alternative to TME surgery. Funding: Medical Faculty Tübingen.
CRIS-Team Scopus Importer:2025-05-16

Phase II Study: Accelerated Partial Breast Irradiation (APBI) on a Linear Accelerator - Ott, Oliver; Schweizer, Claudia; Strnad, Vratislav; Stillkrieg, W.; Lambrecht, U.; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Plan robustness analysis for threshold determination of SGRT-based intrafraction motion control in 3DCRT breast cancer radiation therapy - Sauer, Tim-Oliver; Stillkrieg, Willy; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2023)
Purpose: The goal of this study was to obtain maximum allowed shift deviations from planning position in six degrees of freedom (DOF), that can serve as threshold values in surface guided radiation therapy (SGRT) of breast cancer patients. Methods: The robustness of conformal treatment plans of 50 breast cancer patients against 6DOF shifts was investigated. For that, new dose distributions were calculated on shifted computed tomography scans and evaluated with respect to target volume and spinal cord dose. Maximum allowed shift values were identified by imposing dose constraints on the target volume dose coverage for 1DOF, and consecutively, for 6DOF shifts using an iterative approach and random sampling. Results: Substantial decreases in target dose coverage and increases of spinal cord dose were observed. Treatment plans showed highly differing robustness for different DOFs or treated area. The sensitivity was particularly high if clavicular lymph nodes were irradiated, for shifts in lateral, vertical, roll or yaw direction, and showed partly pronounced asymmetries. Threshold values showed similar properties with an absolute value range of 0.8 mm to 5 mm and 1.4° to 5°. Conclusion: The robustness analysis emphasized the necessity of taking differences between DOFs and asymmetrical sensitivities into account when evaluating the dosimetric impact of position deviations. It also highlighted the importance of rotational shifts, especially if clavicular lymph nodes were irradiated. A practical approach of determining 6DOF shift limits was introduced and a set of threshold values applicable for SGRT based patient motion control was identified.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Intrafraction motion; Probabilistic dose evaluation; Surface guided radiation therapy; Treatment plan robustness

Prerequisites for the clinical implementation of a markerless SGRT-only workflow for the treatment of breast cancer patients - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Purpose: A markerless workflow for the treatment of breast cancer patients has been introduced and evaluated retrospectively. It includes surface-guided radiation therapy (SGRT)-only positioning for patients with small cone beam CT (CBCT) position corrections during the first five fractions. Prerequisites and the frequency of its clinical application were evaluated, as well as potential benefits in terms of treatment time and dose savings, the frequency of CBCT scans, and the accuracy of the positioning. Methods: A group of 100 patients treated with the new workflow on two Versa HD linacs has been compared to a matched control group of patients treated with the former workflow, which included prepositioning with skin markings and lasers, SGRT and daily CBCT. The comparison was based on the evaluation of logfiles. Results: Of the patients treated with the new workflow, 40% did not receive daily CBCT scans. This resulted in mean time savings of 97 s, 166 s and 239 s per fraction for the new workflow, for patients treated without daily CBCT and for SGRT-only fractions, respectively, when compared to the old workflow. Dose savings amounted to a weighted computed tomography dose index reduction of CTDIW = 2.56 cGy on average for normofractionated treatment and weekly CBCTs, while for patients not treated with daily CBCT, SGRT-based positioning accuracy was 5.2 mm for the mean translational magnitude, as evaluated by CBCT. Conclusion: For 40% of the patients, after five fractions with small CBCT corrections, the workflow could be changed to SGRT-only positioning with weekly CBCT. This leads to imaging dose and time savings and thus also reduced intrafraction motion, potentially increased patient throughput and patient comfort, while assuring appropriate positioning accuracy.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Breast neoplasms; Interfraction motion management; Intrafraction motion management; Markerless radiation therapy; Surface-guided radiation therapy

Regional hyperthermia for soft tissue sarcoma–a survey on current practice, controversies and consensus among 12 European centers - Roohani, Siyer; Ehret, Felix; Beck, Marcus; Veltsista, Danai P.; Nadobny, Jacek; Zschaeck, Sebastian; Abdel-Rahman, Sultan; Eckert, Franziska; Flörcken, Anne; Issels, Rolf D.; Klöck, Stephan; Krempien, Robert; et al. (International Journal of Hyperthermia, 2024)
Purpose: To analyze the current practice of regional hyperthermia (RHT) for soft tissue sarcoma (STS) at 12 European centers to provide an overview, find consensuses and identify controversies necessary for future guidelines and clinical trials. Methods: In this cross-sectional survey study, a 27-item questionnaire assessing clinical subjects and procedural details on RHT for STS was distributed to 12 European cancer centers for RHT. Results: We have identified seven controversies and five consensus points. Of 12 centers, 6 offer both, RHT with chemotherapy (CTX) or with radiotherapy (RT). Two centers only offer RHT with CTX and four centers only offer RHT with RT. All 12 centers apply RHT for localized, high-risk STS of the extremities, trunk wall and retroperitoneum. However, eight centers also use RHT in metastatic STS, five in palliative STS, eight for superficial STS and six for low-grade STS. Pretherapeutic imaging for RHT treatment planning is used by 10 centers, 9 centers set 40–43 °C as the intratumoral target temperature, and all centers use skin detectors or probes in body orifices for thermometry. Discussion: There is disagreement regarding the integration of RHT in contemporary interdisciplinary care of STS patients. Many clinical controversies exist that require a standardized consensus guideline and innovative study ideas. At the same time, our data has shown that existing guidelines and decades of experience with the technique of RHT have mostly standardized procedural aspects. Conclusions: The provided results may serve as a basis for future guidelines and inform future clinical trials for RHT in STS patients.
CRIS-Team Scopus Importer:2024-05-03
Keywords: controversies; guideline; Hyperthermia; radiotherapy; soft tissue sarcoma

Regional hyperthermia with cisplatin added to gemcitabine versus gemcitabine in patients with resected pancreatic ductal adenocarcinoma: The HEAT randomised clinical trial - Issels, Rolf D.; Boeck, Stefan; Pelzer, Uwe; Mansmann, Ulrich; Ghadjar, Pirus; Lindner, Lars H.; Albertsmeier, Markus; Angele, Martin K.; Schmidt, Michael; Xu, Yujun; Bahra, Marcus; Pratschke, Johann; et al. (European Journal of Cancer, 2023)
Background: Regional hyperthermia (RHT) with cisplatin added to gemcitabine showed efficacy in gemcitabine-pre-treated patients with advanced pancreatic ductal adenocarcinoma. We conducted a randomised clinical trial to investigate RHT with cisplatin added to gemcitabine (GPH) compared with gemcitabine (G) in the adjuvant setting of resected pancreatic ductal adenocarcinoma. Methods: This randomised, multicentre, open-label trial randomly assigned patients to either GPH (gemcitabine 1000 mg/m2 on day 1, 15 and cisplatin 25 mg/m2 with RHT on day 2, 3 and 15,16) or to G (gemcitabine 1000 mg/m2 on day 1,8,15), four-weekly over six cycles. Disease-free survival (DFS) was the primary end-point. Secondary end-points included overall survival (OS) and safety. Results: A total of 117 eligible patients (median age, 63 years) were randomly allocated to treatment (57 GPH; 60 G). With a follow-up time of 56.6 months, the median DFS was 12.7 compared to 11.2 months for GPH and G, respectively (p = 0.394). Median post-recurrence survival was significantly prolonged in the GPH-group (15.3 versus 9.8 months; p = 0.031). Median OS reached 33.2 versus 25.2 months (p = 0.099) with 5-year survival rates of 28.4% versus 18.7%. Excluding eight patients who received additional capecitabine in the G-arm (investigators choice), median OS favoured GPH (p = 0.052). Adverse events CTCAE (Common Terminology Criteria for Adverse Events) grade ≥3 occurred in 61.5% (GPH) versus 63.6% (G) of patients. Two patients in the G-group died because of treatment-related toxic effects. Conclusions: The randomised controlled Hyperthermia European Adjuvant Trial study failed to demonstrate a significant difference in DFS. However, it suggests a difference in post-recurrence survival and a trend for improved OS. ClinicalTrials: gov, number NCT01077427.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Adjuvant chemotherapy; Cisplatin; Gemcitabine; HEAT study; Pancreatic cancer; Randomised clinical trial; Regional hyperthermia

Region of interest optimization for radiation therapy of breast cancer - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose: The goal of this study was to investigate how the choice of the region of interest (ROI) affects the registration results of surface imaging for daily positioning of breast cancer patients. Methods: The AlignRT system (VisionRT, London) and the XVI Cone beam CT (CBCT; Elekta, Stockholm) installed on two Versa HD linacs (Elekta) were used in this study, which included 28 patients (160 fractions). In the clinical workflow, patients were prepositioned with AlignRT and then shifted in 6 degrees of freedom (DOF) according to the CBCT. A new reference capture was taken immediately afterward. Retrospectively, the surface capture resulting from prepositioning was registered to the latest reference capture. By varying the ROI used for registration, the surface-based results were optimized in terms of minimizing the deviation to the clinically applied CBCT shifts. Two sets of ROIs were used: one obtained by applying a variable margin to the breast surface, another by combining ROIs of anatomical structures, including the sternum and contralateral breast. Results: Registration results showed significant differences from one ROI to another. Generally, the results improved with increasing ROI size, especially for rotational DOFs. ROIs, including the axilla or supraclavicular lymph drainage region, did not yield an improved registration result. On the other hand, an ROI comprising the breast surface, sternum, and a belt caudal to the breasts decreased the average magnitude of the translational and rotational deviations by 6.6% and 30.8% (p < 0.01), respectively, compared to the breast surface only results. Conclusion: The influence of the ROI choice on surface imaging registration results was analyzed and the surface-based shifts were compared to clinically applied CBCT shifts. An optimal ROI for the treatment of breast cancer patients, consisting of the breast surface, sternum, and a belt, was identified.
CRIS-Team Scopus Importer:2021-10-01
Keywords: breast cancer; radiation therapy; surface guided radiation therapy

Risk analysis for radiotherapy at the Universitätsklinikum Erlangen - Lohmann, Daniel; Lang-Welzenbach, Marga; Feldberger, Lorenz; Sommer, Ellen; Bücken, Stefan; Lotter, Michael; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Risk analysis is required by various laws and regulations in Germany and has an impact on each department of a large clinic. We provide an overview of the relevant laws and regulations in Germany and present the technical and organizational experience of introducing risk analysis in the Department of Radiation Oncology at the Universitätsklinikum Erlangen. Methods: Risk analysis was performed with an in-house developed extension of our intranet platform and ticketing system. Risks were classified according to occurrence and severity, each on a 5-level scale resulting into a risk matrix. An interdisciplinary team of six experienced members formed the core meeting weekly. Results: A total of 38 risks and 50 measures have been identified in 41 1 h-meetings corresponding to approx. 260 working hours. Risk was distributed 8/20/13 to the categories critical (n = 8), monitoring (n = 20), and conditionally acceptable (n = 13). Risk analysis has been evaluated before and after introducing measures. Conclusion: The risk analysis method introduced has been successfully used in routine operations for over a year. Risk analysis takes time and effort. However, because experts from different disciplines meet each other every week, the overall workflow of the radiation oncology department can be improved efficiently and continuously.
CRIS-Team Scopus Importer:2022-04-01
Keywords: GBA; Radiation therapy; Risk analysis; Strahlenschutzverordnung

Salvage-radiation therapy and regional hyperthermia for biochemically recurrent prostate cancer after radical prostatectomy (Results of the planned interim analysis) - Beck, Marcus; Ghadjar, Pirus; Mehrhof, Felix; Zips, Daniel; Paulsen, Frank; Wegener, Daniel; Burock, Susen; Kaul, David; Stromberger, Carmen; Nadobny, Jacek; Ott, Oliver; Fietkau, Rainer; et al. (Cancers, 2021)
Efforts to improve the outcome of prostate cancer (PC) patients after radical prostatectomy (RP) include adjuvant or salvage radiation therapy (SRT), but still up to 50% of patients develop a disease progression after radiotherapy (RT). Regional hyperthermia (HT) is well-known to improve tumor sensitivity to RT in several entities. Here we report on a planned interim analysis of tolera-bility and feasibility after recruitment of the first 50 patients of a trial combining SRT and HT. We conducted a prospective multicenter non-randomized Phase-II-Trial (HTProstate-NCT04159051) in-vestigating the implementation of combined moderate-dose escalated SRT (70 Gy in 35 fractions) and locoregional deep HT (7–10 HT sessions). The primary endpoints were the rate of acute genito-urinary (GU), gastrointestinal (GI), and HT-related toxicities, completed HT sessions (≥7), and SRT applications per protocol (≥95% of patients). The two-step design included a planned interim analysis for acute GU-, GI-and HT-specific toxicities to ensure patients’ safety. Between November 2016 and December 2019, 52 patients entered into the trial. After 50 patients completed therapy and three months of follow-up, we performed the planned interim analysis. 10% of patients developed acute grade 2 GU and 4% grade 2 GI toxicities. No grade ≥3 GU or GI toxicities occurred. HT-specific symptoms grade 2 and 3 were observed in 4% and 2% of all patients. Thus, the pre-specified criteria for safety and continuation of recruitment were met. Moreover, ≥7 HT treatments were applicable, indicating the combination of SRT + HT to be feasible. Evaluation of early QoL showed no significant changes. With its observed low rate of GU and GI toxicities, moderate and manageable rates of HT-specific symptoms, and good feasibility, the combined SRT + HT seems to be a promising treatment approach for biochemical recurrence after RP in PC patients.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dose-escalation; Hyperthermia; Postoperative; Prostate cancer; Radiosensitiza-tion; Salvage radiation therapy

Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Raptis, Dimitrios; Maak, Matthias; Krautz, Christian; Merkel, Susanne; Brunner, Maximilian; Agaimy, Abbas; Hartmann, Arndt; Semrau, Sabine; Ott, Oliver; Fietkau, Rainer; Siebler, Jürgen; Grützmann, Robert; et al. (Archives of Medical Science, 2024)
Introduction: Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival. Material and methods: Between 2001 and 2014, 590 patients with a diagnosis of gastric cancer underwent surgery in our institution, including 120 Siewert type II/III carcinomas of the esophagogastric junction. All patients underwent distal resection of the stomach, gastrectomy or total gastrectomy combined with transhiatal distal esophageal resection. All operations included D2-D3 lymph node dissection (LND). Data were recorded by the cancer registry of the department of surgery and analyzed retrospectively. Results: The patients were classified according to the TNM (UICC 2010) and Lauren classification. 29% of the patients underwent primary surgery and 31% received neoadjuvant therapy. The median number of harvested lymph nodes was 33 for patients diagnosed with gastric cancer, and 29 for esophagogastric adenocarcinomas, respectively. The anastomotic leak rate was 3%. In this study, the 5-year overall survival rate was 51% concerning gastric carcinomas, 44% for Siewert type II and 47% for Siewert III cancers of the esophagogastric junction. Conclusions: Increased survival with low complication rates were achieved after individualized and multimodal treatment concepts combined with consistently applied extended lymphadenectomy.
CRIS-Team Scopus Importer:2024-04-19
Keywords: D3 dissection; gastric cancer; Siewert II/III

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The Emerging Evidence Supporting Integration of Deep Regional Hyperthermia With Chemoradiation in Bladder Cancer - Ott, Oliver; Gaipl, Udo; Lamrani, Allison; Fietkau, Rainer (Seminars in Radiation Oncology, 2023)
For decades, the antineoplastic potential of hyperthermia alone or in combination with radiotherapy and/or chemotherapy has been subject of intensive preclinical and clinical research in various tumor entities. The clinical evidence on the beneficial effects of additional hyperthermia in combination with intravesical Mitomycin C for superficial non-muscle-invasive bladder cancer as well as for deep regional microwave hyperthermia techniques applied during an external beam radiotherapy or chemoradiation treatment for more advanced tumors are summarized. In some series, deep regional hyperthermia in combination with an initial transurethral resection and Cisplatin-based chemoradiation increased the 5-year overall survival rates up to 20%. The presented data justifies a fresh irrespective chance for mild regional hyperthermia in the context of new progressive prospective trials on multimodality treatment for bladder preservation.
CRIS-Team Scopus Importer:2022-12-23

The IMMO-LDRT01 Study - Analgesic and immunomodulatory Effects of LDRT in Patients with chronic degenerative and inflammatory Diseases - Donaubauer, Anna-Jasmina; Fröhlich, Birgitta; Becker, Ina; Weissmann, Thomas; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Total Neoadjuvant Therapy as Organ Preserving Therapy for Rectal Cancer: The CAO/ARO/AIO-16 Phase II Study - Gani, C.; Polat, B.; Ott, Oliver; Germer, E.; Koenigsrainer, A.; Kirschniak, A.; Clasen, S.; Grosse, U.; Diefenhardt, M.; Reibetanz, J.; Bitzer, M.; Martus, P.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Tumor-Associated Neutrophils Are a Negative Prognostic Factor in Early Luminal Breast Cancers Lacking Immunosuppressive Macrophage Recruitment - Schmidt, Eva; Distel, Luitpold; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie-Charlotte; Ott, Oliver; Strnad, Vratislav; Hack, Carolin; Hartmann, Arndt; Hecht, Markus; Fietkau, Rainer; Schnellhardt, Sören (Cancers, 2024)
Background: Tumor-associated neutrophils (TANs) are important modulators of the tumor microenvironment with opposing functions that can promote and inhibit tumor progression. The prognostic role of TANs in early luminal breast cancer is unclear. Methods: A total of 144 patients were treated for early-stage hormone-receptor-positive breast cancer as part of an Accelerated Partial Breast Irradiation (APBI) phase II trial. Resection samples from multiple locations were processed into tissue microarrays and sections thereof immunohistochemically stained for CD66b+ neutrophils. CD66b+ neutrophil density was measured separately in the stromal and intraepithelial compartment. Results: High stromal and intraepithelial CD66b+ TAN density was a negative prognostic factor in central tumor samples. In addition, neutrophil density in adjacent normal breast tissue and lymph node samples also correlated with reduced disease-free survival. TAN density correlated with CD163+ M2-like tumor-associated macrophage (TAM) density, which we analyzed in a previous study. TANs were a negative prognostic factor in tumors with an elevated M1/M2 TAM ratio, while this impact on patient outcome was lost in tumors with a low M1/M2 ratio. A combined multivariate analysis of TAM and TAN density revealed that only TAM polarization status was an independent prognostic factor. Conclusions: CD66b+ neutrophils were a negative prognostic factor in early-stage luminal breast cancer in single-marker analysis. Combined analysis with TAMs could be necessary to correctly evaluate their prognostic impact in future studies. TAN recruitment might act as a compensatory mechanism of immunoevasion and disease progression in tumors that are unable to sufficiently attract and polarize TAMs.
CRIS-Team Scopus Importer:2024-10-11
Keywords: breast cancer; CD66b; luminal; tumor-associated macrophages; tumor-associated neutrophils

Tumour-infiltrating inflammatory cells in early breast cancer: An underrated prognostic and predictive factor? - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
The role of tumour-infiltrating inflammatory cells (TIICs) in the disease progression of hormone-receptor-positive breast cancer (HR+ BC) is largely unclear since it is generally regarded as the least immunogenic BC subtype. This study investigated the prognostic significance of CD1a+ dendritic cells, CD20+ B cells, CD45RO+ memory T cells and CD4+ T-helper cells in HR+ BC. One hundred and forty-six patients were treated for early stage, distant-metastases-free HR+ BC in an accelerated partial breast irradiation (APBI) phase II trial. Immunohistochemistry was used to double-stain two adjoining sets of tissue microarrays from pre-RT (radiotherapy) tumour resection samples for CD1a/CD20 and CD45RO/CD4. Cell densities of CD1a+, CD20+, CD45RO+ and CD4+ TIICs in the stromal and intraepithelial compartment were registered semiautomatically. High densities of CD20+ and CD4+ TIICs were strongly associated with reduced disease-free survival (DFS), while high stromal CD45RO+ TIIC densities were indicators of subsequent successful treatment. An immunoscore based on CD20+ and CD45RO+ TIIC densities identified three different risk groups (p < 0.001). Thus, contrary to current assumptions, intratumoural immune cell composition might be an important prognostic indicator and a possible contributing factor in the outcome of HR+ BC and should be the subject of further research. Specifically, B-cell infiltration entailed an increased relapse rate and could play an important role in disease progression.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Accelerated partial breast irradiation; Breast cancer; CD1a; CD20; CD4; CD45RO; Hormone receptor positive; Immunoscore; Prognosis; TIL